MEDIATING DIGITAL BEHAVIOR TO IMPROVE BUSINESS PERFORMANCE IN IKN BUFFER ZONE - Damai N. H., Prasis; Rahmah, Khairunnisa; Satyaninggrat, Luh Made Wisnu (Jurnal Aplikasi Manajemen, 2023)
The existence of the Ibu Kota Nusantara (IKN) is a momentum for businesses in East Kalimantan as a buffer zone to encourage economic growth. However, there are several issues related to the quality of human resources and technical and non-technical skills, weaknesses in capturing opportunities, and lack of innovation. Businesses need to be continuously developed in terms of both quality and skills, especially in digital behavior as a contributor to business performance. Therefore, this study examines factors that are directly and indirectly related to business performance. This research empirically predicts that digital experience and digital literacy can influence digital behavior. Furthermore, this study proposes the relationship between digital experience, digital literacy, and digital behavior to business performance. This study was conducted by taking samples in the IKN buffer zone. Subject was conducted on 80 business owners in Somber Small Industry Center. Data analysis in this study used Warp-PLS. Results of hypothesis testing show that digital literacy has a positive and significant effect on digital behavior. Digital experience has a significant effect on digital behavior. Furthermore, digital behavior has a significant effect on business performance. Partially, digital behavior significantly mediates the relationship between digital literacy and digital experience on business performance. The implications of this study indicate that digital information literacy, service availability, visual quality and access stability are needed to encourage operational performance, management and support performance. Future research recommendations are to examine digital literacy and digital experience variables that have a direct effect on business performance.